PREDICTION OF TREATMENT EFFECTIVENESS IN PATIENTS WITH ASTHMA-COPD OVERLAP COMBINED WITH HYPERTENSION - Hanna Tymchenko (Eastern Ukrainian Medical Journal, 2020)
Introduction. Recently, there has been an increase in the prevalence of comorbid conditions, including a combination of bronchial asthma and chronic obstructive pulmonary disease, called asthma-chronic obstructive pulmonary disease overlap, and their combination with hypertension. The presence of combined pathology causes an increase in the severity of symptoms and functional disorders, in numbers of exacerbations, deterioration of quality of life and tolerance to exercise, and also causes difficulties in selecting a comprehensive treatment for this group of patients. That is why the aim of our study was to optimize and predict the effectiveness of treatment of patients with bronchial asthma in combination with chronic obstructive pulmonary disease on the background of hypertension based on assessing the dynamics of clinical and laboratory and functional status in different treatment regimens.Materials and methods. 100 patients with bronchial asthma in combination with chronic obstructive pulmonary disease on the background of hypertension were selected. Patients underwent: general clinical examination, determination of respiratory function, clinical blood tests and enzyme-linked immunosorbent assays, questionnaires to determine symptoms and quality of life, as well as a functional study with a six-minute walk test in the dynamics of complex basic treatment with physical rehabilitation program.Research results. Adding an active rehabilitation program to standard medical treatment significantly improves the bronchial response to the action of bronchodilators according to the spirometry, reduces clinical manifestations, shortness of breath and improves quality of life and exercise tolerance. The presence of such criteria as the forced expiratory volume in 1 second < 69%, the forced expiratory flow 50% < 21.6% and the forced expiratory flow 75% < 31.65%, C-reactive protein > 7.6 g / l, interleukin 8 > 18.13 pg / ml may provide tolerance to the program of physical rehabilitation and the inexpediency of its use.Conclusions. Under the influence of rehabilitation measures applied by us, patients experienced some positive changes in cardiovascular and respiratory function, exercise tolerance, and quality of life, although some patients do not respond to the addition of a comprehensive rehabilitation program associated with such baseline parameters as forced expiratory volume in 1 second, forced expiratory flow 50% and the forced expiratory flow 75%, C-reactive protein, interleukin 8